Thinking home
1 online resource.
Keywords: Thinking Home challenges and extends the existing scholarship on the subject of home' in a period which has seen unprecedented levels of movement cross the globe. Sanja Bahun and Bojana Petric have collated essays that revisit existing ideas to introduce new ways of thinking on home, from the individual and local, through communal, to the international levels. While home informs our feelings of belonging and displacement, and our activities, such as migration, housing, and language learning, Bahun, Petric and contributors look to specific under-studied areas and encompass them within a major framework that allows for assessment through multiple disciplinary and expressive lenses. Thinking Home examines examples such as temporary homes, homes on the road, new and emergent modes of home-making, and minority groups in home and housing debates. Fresh, timely and topical, Thinking Home is rooted in activism and policy-making in the sector of 'home'; the essays both challenge and extend the existing scholarship on this subject. This collection combines perspectives of aesthetics, anthropology, cultural and literary studies, law, linguistics, philosophy, sociology, psychoanalysis, political science and activist responses in one whole. It will be essential reading for students of anthropology, literary studies, cultural studies and philosophy.